A Rural School/Community: A Case Study of a Dramatic Turnaround and Its Implications for School Improvement - Robert V. Carlson (Journal of Research in Rural Education, 1990)
Valley View is a typical New England smallrural community located in northeastern Vermont which recently approved a bond issue to construct a much needed new elementary school. Community approval of this bond issue represented a significant eventanda reversal ofnearly two decades ofschool/community turmoil. To better understand the dynamics ofthe dramatic turnaround acase study was conducted. Reported in this article are the results of this investigation and their implications for addressing rural scnooi/communlty improvement needs. Current organizational and systems theory were used to isolate significant influences on Valley View and its school. These analyses offer a fresh view at understanding the change process particularly in rural settings.